Inclusive Education and COVID-19: a phenomenological study - Rivera Arellano, Edith Gissela; Méndez Vergaray, Juan; Huayta Franco, Yolanda Josefina; Garro-Aburto, Luzmila Lourdes; Vela Meléndez, Lindon; Reynosa Navarro, Enaidy (Revista Cubana de Investigaciones Biomédicas, 2022)
Objective: To systematize the pedagogical experiences of four Peruvian teachers of Inclusive Education in Peru, COVID-19 context. Methods: Hermeneutical phenomenology proposal with a qualitative approach, which used the in-depth interview to gather information concerning the categories: Teacher; School; Students and parents; Pandemic situation; and Stress, coping and perspectives. The study intervention was planned in three stages: 1. Descriptive: it allowed planning, preparing technical documents, sensitizing participants, and recommending ethical intervention protocols. 2. Structural: it allowed workshops among researchers to practice intervention procedures, review contingency plans and specify the essential research skills and attributes to achieve the study’s objective. Also, the preliminary results were shared with the participants before legitimizing the results. 3. Discussion: the results were contrasted with previous studies to elucidate the coherence and/or fundamental contradictions. Results: Among the main findings, stand out the lack of planned teacher training, the economic limitations of teachers and parents, overwork and its effect on the mental health of teachers, possible violations of the legal framework established for care inclusive children in Peru, as well as problems of adaptation to the new educational scenario. Conclusions: economic limitations and connectivity problems limit the teacher’s performance and the normal learning of inclusive children. The work of the inclusive teacher overflows their working hours, causing emotional effects that impact their performance and quality of life. It is imperative to comply with the legal framework that allows the enrollment and enrollment of inclusive students in Peru.